Different abundances of human-biting ticks in two neighboring provinces in Turkey [Türkiye'de i̇ki komşu i̇lde i̇nsanları tutan kene daģılımındaki farklılıklar] - (:unkn) unknown (Veteriner Fakultesi Dergisi, 2011)
In this study, tick samples were examined, which were obtained from humans who applied to the regional hospitals with complaints of tick bites between May and November 2007 in two neighboring provinces, Kocaeli and Sakarya, in Eastern Marmara Region of Turkey. The samples were evaluated in terms of species, developmental stage and season for each province. In the course of the study, totally 3121 ticks were collected. Of those, 1610 ticks were from Kocaeli, 1511 ticks were from Sakarya. Among the total samples Ixodes spp. (52.87%), Hyalomma spp. (41.78%), Rhipicephalus spp. (4.2%), Haemaphysalis spp. (0.7%), Dermacentor spp. (0.35%) and Argas spp. (0.003%) were identified. Additionally, it was seen that one person was bitten by male Rhipicephalus (Boophilus) annulatus and one other was bitten by nymphal stage of Otobius megnini; these species were recorded for the first time in humans in Turkey. Concerning with the incidences of tick species, majority belongs to Hyalomma spp. (60.06%) in Kocaeli and Ixodes spp. (75.65%) in Sakarya. There were somewhat differences also in incidences of other tick species between these provinces. These disparities encountered between two neighboring provinces which have adjacent coordinates and similar climates, showed that the risk of tick bites or characteristic of this risk in a region could vary distinctly in terms of sub-regions which have some specific sub-conditions.
Keywords: Eastern marmara; Human; Tick; Turkey